Molecular characterisation of common Culicoides biting midges (Diptera: Ceratopogonidae) in Ireland - Elsie Isiye; Angela Valcarcel Olmeda; Thomas Curran; David O’Neill; Theo de Waal; Gerald Barry; Aidan O’Hanlon; James O’Shaughnessy; Nicole Keohane McCarthy; Akke Vellinga; Audrey Jenkinson; Alan Johnson; et al. (Parasites & Vectors)
Abstract Background Biting midges of the genus Culicoides (Diptera: Ceratopogonidae) act as vectors for several arboviruses, including bluetongue virus (BTV) and Schmallenberg virus (SBV), which affect livestock health and productivity. In Ireland, limited genetic data are available regarding the diversity of Culicoides species. This study represents the first attempt to characterise Culicoides in this region using molecular techniques. Methods Adult Culicoides samples were captured using Onderstepoort Veterinary Institute (OVI) traps across six locations in Ireland. Subsequent molecular analyses involved polymerase chain reaction (PCR) and sequencing of the cytochrome oxidase subunit 1 (CO1) and the internal transcriber spacer (ITS) barcoding regions to obtain species identities. In addition, using both markers, we inferred the population genetic structure and potential colonisation pathways of Culicoides obsoletus sensu stricto (s. str.), the major vector species in Ireland. Results DNA barcoding facilitated identification of 177 specimens. Eight common Culicoides species were identified through DNA barcoding of CO1 and ITS gene regions. The presence of putative vectors of bluetongue virus (BTV) and Schmallenberg virus (SBV) were also confirmed, including species in the subgenus Avaritia (C. obsoletus s. str., C. scoticus, C. chiopterus, and C. dewulfi) and subgenus Culicoides s. str. (C. pulicaris and C. punctatus). Phylogenetic analysis confirmed the relationship between these vector species and facilitated the placement of Culicoides spp. that could not be identified to species level through DNA barcoding. Haplotype network analysis of C . obsoletus showed that some haplotypes of these species are shared between Continental Europe, the UK, and Ireland, suggesting a possible incursion pathway for this vector. Conclusions DNA barcoding employing a combination of two barcodes, CO1 and ITS, proved effective in identifying Culicoides, especially species within the obsoletus complex, which are difficult to morphologically distinguish. Our findings also suggest that investigation of the population genetic structure of Culicoides spp. could be used to model the potential introduction routes of midge-borne pathogens into the country. Graphical Abstract